The effect of relative density, granularity and size of geogrid apertures on the shear strength of the soil/geogrid interface - Lakirouhani, Ali; Abbasian, Mojgan; Medzvieckas, Jurgis; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2024)
The increasing use of geogrid in various geotechnical projects has made the evaluation of the shear behavior of soil reinforced with geogrid become particularly important. In this article, a series of large-scale direct shear tests have been performed on sand and gravel samples reinforced with geogrid. The purpose of the experiments was to investigate the impact of the geogrid mesh size and the relative density of the samples on the shear strength coefficient of the interface between soil and geogrid. In this study, 5 geogrids with different mesh sizes and one type of geotextile were used. According to the results, the average shear strength coefficient of sand and gravel samples reinforced with geogrid for different normal stresses and different relative densities was obtained between 0.72 and 0.94. As the relative density increases, the interface shear strength coefficient decreases, this means that the denser the sand, the more the shear strength of the sand/geogrid interface decreases. Based on the results, it was found that the contribution of particle interlocking in the shear resistance of the sand/geogrid interface is particularly important, so that the shear resistance coefficient of the interface increases with the increase in the size of the geogrid mesh.